Factors Affecting Utilization of the National Health Insurance Scheme by Federal Civil Servants in Rivers State, Nigeria - Obelebra Adebiyi MPH; Foluke Olukemi Adeniji FWACP (SAGE Publishing, 2021)
The National Health Insurance Scheme (NHIS) of Nigeria was established in 2005. This study assessed the utilization of health care and associated factors amongst the federal civil servants using the NHIS in Rivers state. This was a descriptive cross-sectional study using self-administered questionnaires. Data were collated and analyzed using SPSS version 21.0. A Chi-square test was carried out. The level of Confidence was set at 95%, and the P -value ≤ .05. Out of a total of 334 respondents, 280 (83.8%) were enrolled for NHIS, 203 (72.5%) utilized the services of the scheme. Most 181 (82.1%) of the respondents who utilized visited the facility at least once in the preceding year. Although, 123 (43.9%) of the respondents made payments at a point of access to health care services, overall there was a reduction in out of pocket payment. Possession of NHIS card, the attitude of health workers, and patients' satisfaction were found to significantly affect utilization P  ≤ .05. Regression analysis shows age and income to be a predictor of utilization of the NHIS. Though utilization is high, effort should be made to remove payment at the point of access and improving the harsh attitude of some of the health workers.